HAK-HAK PEREMPUAN PASCA PERCERAIAN: PERBANDINGAN HUKUM KELUARGA ISLAM DI INDONESIA DAN MESIR - Ahmad, Farouq Ali; Rahmawati, Rahmawati; Said, Zainal; Fikri, Fikri; Bakri, Muhiddin; Basri, Rusdaya (IAIN BONE, 2025)
This research discusses women's rights after divorce by comparing Islamic family law in Indonesia and Egypt. The main focus of this research is to answer three questions: 1) how are women's rights post-divorce regulated in Indonesia, 2) how are the same arrangements in Egypt, and 3) comparative analysis between the two countries. The research uses a library method (research library) with a normative juridical approach and data collection techniques through document study. The research results show that in Indonesia, Islamic family law aims to protect women's rights through iddah, mut'ah and madhiyah livelihoods. However, enforcing these rights often faces challenges. In Egypt, Law no. 100 of 1985 provides similar protection, including the right to divorce and maintenance during the iddah period, although its implementation is hampered by social and cultural factors. A comparison between the two countries reveals similarities and differences in the arrangement of these rights. The husband's obligation to provide maintenance during the iddah period in Indonesia is flexible and determined by the court, whereas in Egypt it is more strict. Mut'ah in Indonesia is considered a respect that is not always required, while in Egypt it is the wife's right. In terms of joint assets, Indonesia considers all assets during a marriage to be jointly owned with division based on agreement, while Egypt considers the contribution of each party. This difference is influenced by economic factors, local culture, as well as regulations on interfaith marriages which are prohibited in Indonesia but exist in Egypt.